A unique neutrino mass matrix texture under exponential parametrization - Pralay Chakraborty; Subhankar Roy (Journal of High Energy Physics)
Abstract Under the exponential parametrization scheme m ij ν $$ {m}_{ij}^{ν } $$ ∼ re iθ , we propose a unique neutrino mass matrix texture that exhibits four correlations among its elements. The mixing scheme obtained from the proposed texture is consistent with experimental observations. We construct a concrete model based on the SU(2) L × U(1) Y × A 4 × Z 10 × Z 7 group within the framework of the seesaw mechanism.